(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article provides a historical analysis of the political, military and cultural activities of the rulers of the Eastern Chigatay ulus based on Eastern sources. In particular, the role of the rulers who lived in the XIV-XV centuries in domestic and foreign policy, their state administration, diplomatic relations and attention to science are covered based on the sources. The article is based on historical sources in Arabic, Persian and Turkic languages, in particular, Zafarnama, Tarikhi Rashidi, Muntakhab ut-tavorikh and other works. Also, the statehood traditions, socio-political structure and specific activities of the rulers of the Eastern Chigatay ulus are evaluated using a modern historiographical approach. The results of the research serve to reveal some little-studied aspects of the history of this period.